2008
DOI: 10.1016/j.clim.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of common mitochondrial DNA variants with multiple sclerosis and systemic lupus erythematosus

Abstract: Mitochondrial dysfunction has been implicated in the pathogenesis of multiple sclerosis (MS) and systemic lupus erythematosus (SLE). This study re-investigates the roles of previously suggested candidate genes of energy metabolism (Complex I genes located in the nucleus and in the mitochondria) in patients with MS relative to ethnically matched SLE patients and healthy controls. After stringent correction for multiple testing, we reproduce the association of the mitochondrial (mt) DNA haplotype K* with MS, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 27 publications
0
58
1
3
Order By: Relevance
“…Recently, potential immunogenicity of peroxy-nitrite modified mitochondrial DNA (mtDNA) has been shown in SLE [9]. Additionally, increased serum level of mtDNA was detected in patients diagnosed with various neurodegenerative disorders, such as autism, Parkinson disease and multiple sclerosis [10,11,12]. Several authors have suggested that mtDNA can act as trigger points for the development of autoimmune disorders as well [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, potential immunogenicity of peroxy-nitrite modified mitochondrial DNA (mtDNA) has been shown in SLE [9]. Additionally, increased serum level of mtDNA was detected in patients diagnosed with various neurodegenerative disorders, such as autism, Parkinson disease and multiple sclerosis [10,11,12]. Several authors have suggested that mtDNA can act as trigger points for the development of autoimmune disorders as well [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increased serum level of mtDNA was detected in patients diagnosed with various neurodegenerative disorders, such as autism, Parkinson disease and multiple sclerosis [10,11,12]. Several authors have suggested that mtDNA can act as trigger points for the development of autoimmune disorders as well [10,13]. Although immune reactivity towards nucleic acids is well established, it remains to determine which type of nucleic acids are more immunogenic in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…5 The association of the K haplogroup with adult MS risk has recently been replicated. 6 Other mtDNA variants, such as 13966G or 14798C, have been published in rare case reports of patients with MS. 7 A restriction endonuclease splice variant in the 15927/15928 region of the mitochondrial tRNA (thr) gene was reportedly more frequent in patients with MS with severe optic neuropathy compared to controls, although the specific mutation responsible for this association was not identified. 8 An increased frequency of MS also has been reported in pedigrees of patients with Leber hereditary optic neuropathy (LHON), 9 which is caused by mutations in mtDNA, and optic nerve involvement is common in both conditions.…”
mentioning
confidence: 99%
“…To a large degree it is secondary to the chronic inflammation that occurs during the course of disease progression and/or during active disease. It may originate from many non-NADPH oxidase sources such as dysfunctional mitochondria in lupus T-lymphocytes linked to enhanced mitochondrial oxygen consumption (42) or polymorphisms in mitochondrial DNA complex I (43).…”
Section: Discussionmentioning
confidence: 99%